THE EFFECT OF DIFFERENT TYPE OF SERA ON MATURATION RATE OF BUFFALO FOLLICULAR OOCYTES - MISTRY, C N; DHAMI, A J; SUTHAR, V S; JOSHl, C G; RANK, D N (The Indian Journal of Animal Reproduction, 2023)
A total of 1409 follicular oocytes were recovered by slicing method from 456 ovaries of Surti buffaloes collected from the local abattoir. The object was to assess the effect of different categories of buffalo sera (20%, with natural hormones) in relation to BSA (0.6%, Sigma, supplemented with 10 IU/ml of eCG - Folligon and 5 IU/ml of hCG - Chorulon, lntervet) on in vitro maturation (IVM) of oocytes in TCM-199 medium. The sera were obtained locally from different categories of animals, viz., fetal bovine serum (FBS, Gibco), neonatal buffalo serum (NBS), oestrus buffalo serum (OBS), post-oestrus buffalo serum (POSS), and anoestrus buffalo serum (AnBS) and processed further for heat inactivation in the laboratory. The oocyte recovery rate was 3.09 per ovary. The average oocyte recovery of grade A, grade Band grade C was 1.02, 1.22 and 0.85, respectively. The maturation rate in presence of POBS, AnBS, FBS, NBS and OBS, each at 20 % level in TCM-199 medium, was found to be 64.63, 54.55, 70.63, 60.48 and 78.16 per cent, respectively, as against 84.00 per cent with 0.6 % BSA supplemented with hormones. The culture medium containing oestrus buffalo serum (OBS) yielded significantly higher (P<0.05) maturation rate (at par with BSA) than the other sera used. The highest maturation (90.00 %) of gradeAoocytes was found in BSA0.6 % followed by OBS (86.67 %) and other sera, while In grade . Bit was in BSA0.6 % (82.61 %), OBS (81.58%) and FBS (80.00%)-all at par, and for grade C oocytes the higher (P<0.05) maturation rate was with BSA0.6 % (80.56 %) as compared to all sera.According to nuclear maturation, the highest number of oocytes with germinal vesicle was found in medium containing NBS (25.81 %)followed byAnBS (18.18 %) and others. The highest number of GVBDwas . found in POBS (30.61 %) followed by FBS (29.37 %). The higher number of oocytes with Metaphase- 1 was in the medium containing BSA0.6 % (22.13 %)followed by FBS, while, the Metaphase-11 stage was found to be higher in medium containing OBS (41.38 %) followed by BSA 0.6 per cent (35.25 %). The degenerated oocytes were lowest in OBS (9 .20 % ) and highest in AnBS (27 .27 % ). Overall, the 20 % OBS plain appeared to be an alternate to 0.6% BSA with 10 IU/ml of eCG and 5 IU/ml of hCG for IVM of buffalo follicular oocytes.